The Relationship between Tourism Industry and Economic Growth in India: Evidence from Multivariate Regression Analysis - Prakash, Bishwajeet; Kumar, Vijay; Gautam, Rakesh Kumar (Revista de turism - studii și cercetări în turism, 2020)
Tourism industry of any country is not only related with the economic profit of the country but it is also a way to communicate heritage, cultural, social and environmental values between two nations. Tourism industry in India contributed 9.6 per cent in total GDP of country in 2016 with the value US $ 71.55 billion and it is third largest sector contributed in foreign exchange earnings. The estimated compound annual growth rate for direct contribution of tourism and hospitality industry to GDP for 2016-17 was 14.05 per cent. As per the report of world travel and tourism council’s economic impact 2017 forecasted contribution of tourism industry to GDP by 2027 is 147.96 billion. In 2016, 8.8 million foreign tourists arrived in India which is forecasted 15.3 million by 2025. The present study is designed to analyze the growth rate of tourism industry in India. The finding of the study suggests that Foreign Exchange Earnings (FEE) from the foreign tourists is significant for Gross Domestic Product (GDP) of India whereas the impact of Foreign Tourist Arrivals (FTA) on Gross Domestic Product (GDP) in India is not significant.